Investigation of pyrolysis behavior shale gas oil-based drilling cuttings kinetics and product characteristics - Pu Liu; Wei Li; Ruifeng Tan; Liu Zhongbin; Zhang Bin (Scientific Reports)
Abstract Oil-based drill cuttings (OBDC) are a typical hazardous waste generated during the development of shale gas fields, and pyrolysis can recover harmful components for resource recycling. This study evaluates the pyrolysis behavior through the study of pyrolysis kinetics and analyzes the impact of pyrolysis temperature on the yield of gaseous products, the quality of liquid products, and the migration of heavy metals in the solid phase. The results indicate that the pyrolysis of OBDC is divided into three stages, with the activation energy increasing as the reaction progresses. Moreover, the temperature at which the maximum weight loss rate occurs under high heating rates is higher. The four typical methods selected (FM, OFW, KAS, and Starink) all provide excellent fits to the weight loss curves. The pyrolysis temperature significantly affects the distribution of products; as the temperature rises, the total gas yield increases to varying degrees, the liquid phase undergoes degradation, resulting in the formation of new complex substances, and the solid phase content gradually increases. Additionally, after thermal treatment at corresponding times, the content of coke and the recovery rate of mineral oil in OBDC change differently. The heavy metals Pb, Zn, Mn, and Cr in the coke show the same trend in content and residual rate after pyrolysis treatment, with Cr, Cu, and Zn being enriched and fixed in the coke, indicating that pyrolysis has a certain effect on the stabilization of heavy metals in oil-based drill cuttings. This information on the solid products generated from the pyrolysis of industrial OBDC alerts future researchers to pay attention to the final disposal of the entire technical output.